Multiple-Ring-Core FM-EDF for Weakly-Coupled MDM Amplification With Low Differential Modal Gain - Jinglong Zhu; Mingqing Zuo; Yu Yang; Dawei Ge; Lei Shen; Zhangyuan Chen; Yongqi He; Juhao Li (IEEE Photonics Journal)
Recently weakly-coupled mode-division multiplexing (MDM) transmission systems and networks based on ultralow-modal-crosstalk few-mode fiber (FMF) have attracted much interest, for which optical amplification technologies with low modal crosstalk and two-dimension mode-wavelength gain flattening are highly desired. In this paper, we propose for the first time a design method for few-mode Erbium-doped fiber (FM-EDF) with multi-ring-core (MRC) structures of both index and Erbium doping, which has high compatibility with the transmission MRC-FMF and low differential modal gain (DMG) with simple pump injection requirement. By sharing the boundaries of ring areas for both index and Erbium doping, the design method also helps to reduce the complexity of preform fabrication. We show by simulation that at 1550-nm signal wavelength, a 6-mode MRC-EDF can achieve a minimum DMG of 0.35-dB with only LP11 pump light injection and a 10-mode MRC-EDF can achieve a minimum DMG of 0.60-dB with LP01 and LP03 pump lights injection. Besides, the tolerance of DMG to the variation of fiber parameters induced by fabrication is analyzed. The proposed FM-EDF is beneficial for the practical applications of weakly-coupled MDM transmission systems and networks.